How to Be a Farmer : An Ancient Guide to Life on the Land - Usher, M. D. (Mark David), 1966-; Usher, M. D. (Mark David), 1966- (Book collections on Project MUSE., 2021)
"An assemblage of selections from classical literature that celebrate country living-what Roman authors called res rusticate"--